652 LAPAROSCOPIC FUNDOPLICATION IS EFFECTIVE TREATMENT FOR PATIENTS WITH GASTROESOPHAGEAL REFLUX AND ABSENT ESOPHAGEAL CONTRACTILITY. (17th September 2021) - Tran, Steven; Gray, Ronan; Kholmurdova, Feruza; Thompson, Sarah; Myers, Jennifer; Bright, Tim; Irvine, Tanya; Watson, David
Abstract: : Anti-reflux surgery in the setting of preoperative esophageal dysmotility is contentious due to fear of persistent long-term dysphagia, particularly in individuals with an aperistaltic esophagus (absent esophageal contractility). Emerging evidence suggests fundoplication is safe and effective in patients with esophageal dysmotility. This study aimed to determine the long-term postoperative outcomes following fundoplication in patients with absent esophageal contractility versus normal motility. Methods: A case control study was performed, using a prospectively maintained database to identify all (40) patients with absent esophageal contractility on preoperative manometry who subsequently underwent fundoplication (36 anterior partial, 4 Nissen). Cases were propensity matched based on age, gender, and fundoplication type with another 708 patients who all had normal motility. Groups were assessed using prospective symptom assessment questionnaires to assess heartburn, dysphagia for solids and liquids, regurgitation, and satisfaction with surgery. Outcomes were compared at baseline and at 1, 5 and 10 years follow-up. Results: Across follow-up to 10 years, no significant differences were found between the two groups for any of the assessed postoperative symptoms. Multivariate analysis found that patients with absent contractility had worse preoperative dysphagia (adjusted mean difference 1.09, p = 0.048), but postoperatively there were no significant differences in dysphagia scores at 5 and 10 year follow-up. No differences in overall patient satisfaction were identified across the follow-up period. Conclusion: Laparoscopic anterior partial fundoplication in patients with absent esophageal contractility achieves acceptable symptom control without significantly worse dysphagia compared to patients with normal contractility. Patients with medically refractory reflux who have absent contractility should still be considered for surgical intervention.